A case report and literature review on TP53 gene mutation in a bladder rhabdomyosarcoma patient - Li, Yixuan; Yang, Tianci; Zheng, Zhouhang; Wang, Zhong; Umar, Shahzard Muhammad; Fan, Ning; He, Shenbao; Chang, Wei; Wang, Wei (Frontiers in Oncology, 2024)
Background: Rhabdomyosarcoma of the bladder is an infrequent neoplastic condition characterized by a pronounced malignant situation with challenges in treatment due to the lack of standardized guidelines and large-scale of clinical studies. The patient in this case is tested TP53 mutation that may provide new diagnostic and therapeutic options.Case presentation: Here, we report a 34-year-old male who received bladder tumor resection, and diagnosed as bladder rhabdomyosarcoma with TP53 mutation after the pathology test. This patient underwent 6 rounds of chemotherapy. However, the pelvic tumor recurred 11 months after the first surgery. So, the patient accepted the pelvic tumor resection. Only 3 months after the surgical intervention, the patient underwent abdominal massive metastasis and ultimately succumbed to the illness six months following the second surgery. The course of the illness was 22 months.Bladder rhabdomyosarcoma is a disease with an extremely poor prognosis.Genetic testing holds significant value in the diagnosis and treatment. Perhaps targeted therapy against TP53 is potential valuable for such rare diseases.